Psycholinguistic approaches to production and comprehension in bilingual adults and children - Fernandez, Leigh; Katsika, Kalliopi; Iraola Azpiroz, Maialen; Allen, Shanley (Benjamins current topics, 2021)
"How do production and comprehension processes interact in the bilingual brain during language interaction? Most experimental and theoretical research in psycholinguistics to date has focused on investigating the mechanisms that underlie language production and language comprehension separately. Only recently have researchers started emphasizing the importance of reconciling the two modalities into a unified account through the investigation of possible connections between the two systems. Authored by key researchers in psycholinguistics, neuroscience, and language development, this volume encompasses state of the art research on the relation between production and comprehension processes in bilingual children and adults. Articles highlight the most recent methodological approaches, as well as a variety of language pairs and linguistic structures. Indispensable for students and researchers working in the areas of language acquisition and processing, neurolinguistics, and experimental linguistics, this volume will also appeal to educators and clinicians focusing on language development and processing in multilingual children and adults. Originally published as special issue of Linguistic Approaches to Bilingualism 9:4/5 (2019)"--